Seasonal variation, group/ solitary behavior occurrence and reproduction time of the predator leech Helobdella stagnalis (Hirudenia: Glossiphoniidae) in Sarchnar Stream/ Sulaymaniah Province, Kurdistan Region- Iraq. - Hallaq, Shayan; Abdullah, Younis; Samir J. Bilal (Zanco Journal of Pure and Applied Sciences, 2024)
A total of 194 specimens of the predatory leech Helobdella stagnalis were collected from Sarchnar Stream, in Sulaimaniyah City along year of 2022 from January to the end of December. The seasonal distribution and occurrence, time of egg laying and hatching in relation with some physico-chemical factors were studied, including air and water temperatures, dissolved oxygen, pH, FCO2, HCO3-, Cl-, Ca+2 and Mg+. The temperature and dissolved oxygen were the most effective factors on leech’s population density as well as time of egg lying and juvenile hatching. The highest density was in Autumn, while the lowest was recorded during Summer. Cocoons were seen to laid in late winter and maximum juvenile numbers were recorded during Spring.